Tokens of friendship, tools of diplomacy: buttons and medals in exploration*. (3rd July 2017) - Peck, Robert McCracken
ABSTRACT: To help smooth first and early encounters with indigenous people around the world, European and American explorers often presented gifts to the people whose lands they were exploring. Buttons from naval or military uniforms were sometimes exchanged for food, furs, and other local products. Special medals were also prepared for use on expeditions. These were selectively presented to indigenous leaders or left as tangible records of places "discovered" or visited. This paper discusses and illustrates examples of both kinds of gifts.